Shooting the messenger: Mediating the public and the role of the media in South Africa's xenophobic violence - Hadland, Adrian (2010)
In the wake of the outbreak of xenophobic violence in South Africa in May 2008, in which sixty people died and tens of thousands were displaced, a fierce debate erupted on the role of the media. The focus of the criticism was South Africa's newly-established tabloid press which is accused of fomenting violence and exacerbating tension by publishing inflammatory headlines and posters. But to what extent can the tabloid press really be blamed for aggravating the conflict? The scholarly literature on media effects suggests that direct causality is hard to prove. The accusation says much, however, about media-statesociety relations in post-apartheid South Africa; it also raises questions about the state of the public sphere and the role of the media within it. Field work conducted by the Human Sciences Research Council in four South African informal settlement areas affected by the recent violence indicates that the tabloids certainly cannot be blamed directly for fanning the violence. But it does seem to confirm what thousands of protests in the past year have strongly hinted at: there has been a communications breakdown in South Africa at a local level between communities and the state, as well as within communities, which lies at the root of much of the anger and violence. By failing to respond to this breakdown and act on its liberal imperative of providing a "voice for the voiceless", the media may be more complicit than it, or the literature, is willing to acknowledge